Tramway à Montréal-1861 à 1959 - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
Keywords: Montreal Street Railway Company; Tramways

De 1800 à 1830. Montréal, jeune métropole britannique - Robert, Jean-Claude (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Métropole; Port

1800 to 1830. Montréal, Building British Metropolis - Robert, Jean-Claude (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne’s Market and the Parliament of the Province of Canada, 2021)
Keywords: Métropole; Port

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Chemins de fer; Musique; Noirs; Travail

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

The Changing of the Guard: Bartlett McLennean, Roy Wolvin, and the Leveraged Buyout of the Montreal Transportation Compagny, 1903-1921 - Salmon, M. Stephen (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Golden Square Mile; Navigation

Ponts et traverses de la rivière des Prairies - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Ponts; Rivière des Prairies; Rivière-des-Prairies

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

Montréal en 1919 : industries, travail et espaces résidentiels - Girard, David (Université du Québec à Montréal, 2020)
Keywords: Tramways; Travail

De la barge aux usines: les mécanismes de déchargement du charbon au canal de Lachine - Paquet, Lucie (Bulletin de l'AQPI, 2021)
Keywords: Lachine (canal); Montreal Rolling Mills

« Dear Richard...send us a few buffalo tongue »: Donald Smith's Fur Trade Contacts and Peronal Credit Networks - Hamon, Max (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Autochtones; Bourgeoisie; Chemins de fer; Femmes; Fourrure; Golden Square Mile

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Chemins de fer; Paysages

La requalification du secteur industriel du Mile End, Montréal - Bur, Justin (Bulletin de l'AQPI, 2022)
Keywords: Canadien Pacifique; Carrière; Chemins de fer; Mile End

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

À la croisée des chemins : mise en place et implantation du réseau de télégraphe électrique canadien, 1846-1867 - Dumais-Gingras, Pierre (Université du Québec à Montréal, 2021)
Keywords: Téléphone

Le pont-tunnel Louis-Hippolyte-La Fontaine : aux origines d'une infrastructure routière régionale - Gaudry, William (Université du Québec à Montréal, 2022)
Keywords: Autoroutes; Ponts; Tunnels